External ultrastructure of Manayunkia speciosa (Fabriciidae) from Uruguay River, Argentina - Paola, Analía C. (2013)
The external ultrastructure of Manayunkia speciosa Leidy, 1858 from specimens collected at the lower Uruguay River, South America is described using scanning-electron-microscopy. The branchial crown has a pair of semicircular lateral lobes, a pair of mediodorsal radioles and a pair of medioventral ones. Radiolar surfaces are ciliated. The faecal groove is observed on peristomium middorsally. The anterior margin of the anterior peristomial ring formed a rectangular lobe, with a ciliated band. Chaetal shape exemplifies the basic type of tapering cylinder. Two types of thoracic notochaetae: one wider distally, with a smooth handle, and covered on the surface by denticles, and other are significantly finer at the base and covered by thin structures with a free distal end. These structures were not previously recorded in Fabriciidae. Rows of 3 aligned uncini anteriorly projected are found in the thorax. Each uncinus presents a long manubrium which connects with the crest, extending to a main fang. The teeth of the crest are equal in size. The abdomen present 4 types of neurochaetae: one of small size than the other 3. In the abdomen 10-14 uncini form dense dorsal-transverse-lines. Each uncinus presents a short manubrium. The crest is covered with teeth of similar size.